2011
DOI: 10.1007/s12070-011-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Hearing Loss Among Mobile Phone Users

Abstract: The objective of this study is to assess high frequency hearing (above 8 kHz) loss among prolonged mobile phone users is a tertiary Referral Center. Prospective single blinded study. This is the first study that used high-frequency audiometry. The wide usage of mobile phone is so profound that we were unable to find enough non-users as a control group. Therefore we compared the non-dominant ear to the dominant ear using audiometric measurements. The study was a blinded study wherein the audiologist did not kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…The widespread use of mobile have raised concerns about the possibility that exposure to the RF fields from mobile phones or their base stations could affect people's health, particular concern to the WHO is the fact that, developing countries are establishing this technology in preference to the more expensive fixed line systems. [6][7][8][9][10][11][12] Keeping in view the hazards of the mobile phones, the present study was designed to investigate the association of use of mobile phones and hearing loss. In our study, mean age was found to be 20.45±1.55 years in group A and 21.85±2.81 years in group B. Patel et al, 6 reported mean age was 26.17±2.65 in study group and that of controls was 26±3.93 years.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of mobile have raised concerns about the possibility that exposure to the RF fields from mobile phones or their base stations could affect people's health, particular concern to the WHO is the fact that, developing countries are establishing this technology in preference to the more expensive fixed line systems. [6][7][8][9][10][11][12] Keeping in view the hazards of the mobile phones, the present study was designed to investigate the association of use of mobile phones and hearing loss. In our study, mean age was found to be 20.45±1.55 years in group A and 21.85±2.81 years in group B. Patel et al, 6 reported mean age was 26.17±2.65 in study group and that of controls was 26±3.93 years.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, aural block sensation (23%) followed by tinnitus (21.15%) and decreased hearing (7.69%) were the presentations among mobile users. Mobile phones have been used since 1983, and their use was estimated to include around 6 billion users in 2010 [5].…”
Section: Discussionmentioning
confidence: 99%
“…The BC threshold of the exposed ear and nonexposed ear show statistically significant difference at the average threshold and threshold of all frequencies. These findings are similar to studies conducted by Ramya et al .,[ 12 ] Prajapati et al .,[ 15 ] Velayutham et al .,[ 16 ] and Panda et al . [ 17 ] and suggest a possible inner ear damage caused by prolonged usage of mobile phones.…”
Section: Discussionmentioning
confidence: 99%